2014
DOI: 10.1002/jhm.2241
|View full text |Cite
|
Sign up to set email alerts
|

Management of calcium channel blocker overdoses

Abstract: Calcium channel blockers (CCBs) are some of the most commonly used medications in clinical practice to treat hypertension, angina, cardiac arrhythmias, and some cases of heart failure. Recent data show that CCBs are the most common of the cardiovascular medications noted in intentional or unintentional overdoses.1 Novel treatment approaches in the form of glucagon, high‐dose insulin therapy, and intravenous lipid emulsion therapies have been tried and have been successful. However, the evidence for these are l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
(156 reference statements)
0
9
0
Order By: Relevance
“…The total number of citations at the time of data analysis (23 October 2014) was 6462, with an average of 9.1 citations per document and a median (interquartile range) of 3(0.0-10.5). The highest median (interquartile range) number of citations was 8 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) for the United States, followed by 6 (1-21) for Australia, 5 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) for the United Kingdom, and 5 for Canada. The h-index of the retrieved documents was 37 (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The total number of citations at the time of data analysis (23 October 2014) was 6462, with an average of 9.1 citations per document and a median (interquartile range) of 3(0.0-10.5). The highest median (interquartile range) number of citations was 8 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) for the United States, followed by 6 (1-21) for Australia, 5 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) for the United Kingdom, and 5 for Canada. The h-index of the retrieved documents was 37 (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 Moreover, of cardiovascular medications, CCBs were the most common agents associated with a significant morbidity and mortality rate. 2,3 CCBs were responsible for at least 78 deaths in 2011 in the United States. 4 CCBs poisoning is on the rise, 4,5 and it has resulted in growing research in many research areas such as emergency medicine 6,7 or cardiovascular 8,9 or clinical toxicology.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,12,[26][27][28][29][30][31][32][33] Although there is no consensus regarding duration of high-dose insulin therapy, many clinicians continue administration until hemodynamic stability is achieved. 36 Potential adverse effects of high-dose insulin include hypoglycemia and hypokalemia. 36 In the documented pediatric case reports using high-dose insulin, only Yuan et al 26 reported hypoglycemia during the highdose insulin infusion, but this event was asymptomatic and easily corrected with a dextrose bolus.…”
Section: Io Intraosseous Infusion; Va-ecmo Venoarterial Extracorporeal Membrane Oxygenationmentioning
confidence: 99%